Ferroelectric, Piezoelectric and Dielectric Behaviors of CoO- and Fe2O3-Doped BCZT Ceramics - Piyaporn Jaimeewong (2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim This study investigates the effect of CoO and Fe2O3 dopant on phase, microstructure and ferroelectric properties of BCZT ceramics with the formula of Ba0.85Ca0.15Zr0.1(Ti1-xCox)0.9O3 and Ba0.85Ca0.15Zr0.1(Ti1-xFex)0.9O3 where x = 0, 0.01, and 0.03. The XRD patterns presented that the pure perovskite phases are observed regardless of the amount of CoO and Fe2O3 added. Rietveld analysis shows that the tetragonal phase is observed in all patterns and the unit cell volume slightly expanded by the CoO addition while it is distorted with increasing Fe2O3 addition. The average grain sizes decreased upon CoO and Fe2O3 addition. It is found that the doping of CoO and Fe2O3 caused the transition temperature to shift to lower temperature. The optimum ferroelectric and dielectric properties can be achieved for the BCZT-0.01Co ceramics. This study shows that while small doping with Co and Fe can enhance different properties of BCZT with lower processing temperature, the properties should be further optimized by chemical modification.